Estudio de las probabilidades de transición de los trabajadores entre el sector formal e informal en Colombia (2018)
Given the fact that the informal sector is commonly associated with developing countries, it has been argued that this sector is a consequence of distortions and rigidness of the labor market that encourages segmentation. Regardless, there is evidence to suggest from Latin-American countries that this view is not realistic and that the magnitude of the informal sector is also a result of autonomous decisions of some workers that consider the informal sector superior. As a result, the present work is an analysis of the worker?s transitions between the formal and informal sector in Colombia. The results gathered, indicate that the nature of the transitions adjust more accurately to that of the segmentation view, although, some cases of voluntary transitions are also observed and are evidenced in the subsequent rise in the welfare of the worker after the transition.